Arabidopsis Fatty Acid Desaturase FAD2 Is Required for Salt Tolerance during Seed Germination and Early Seedling Growth - Zhang, Jiantao; Liu, Hua; Sun, Jian; Li, Bei; Zhu, Qiang; Chen, Shaoliang; Zhang, Hongxia (PLOS ONE, 2012)
Fatty acid desaturases play important role in plant responses to abiotic stresses. However, their exact function in plant resistance to salt stress is unknown. In this work, we provide the evidence that FAD2, an endoplasmic reticulum localized ω-6 desaturase, is required for salt tolerance in Arabidopsis. Using vacuolar and plasma membrane vesicles prepared from the leaves of wild-type (Col-0) and the loss-of-function Arabidopsis mutant, fad2, which lacks the functional FAD2, we examined the fatty acid composition and Na+-dependent H+ movements of the isolated vesicles. We observed that, when compared to Col-0, the level of vacuolar and plasma membrane polyunsaturation was lower, and the Na+/H+ exchange activity was reduced in vacuolar and plasma membrane vesicles isolated from fad2 mutant. Consistent with the reduced Na+/H+ exchange activity, fad2 accumulated more Na+ in the cytoplasm of root cells, and was more sensitive to salt stress during seed germination and early seedling growth, as indicated by CoroNa-Green staining, net Na+ efflux and salt tolerance analyses. Our results suggest that FAD2 mediated high-level vacuolar and plasma membrane fatty acid desaturation is essential for the proper function of membrane attached Na+/H+ exchangers, and thereby to maintain a low cytosolic Na+ concentration for salt tolerance during seed germination and early seedling growth in Arabidopsis.